MODEL DRILL UNTUK MENINGKATKAN KECAKAPAN BERMAIN PESERTA EKSTRA KURIKULER BOLA VOLI DI SMA NEGERI 1 BANDONGAN - Syarif, Ahmad (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
Following Extracurricular Bolavoli SMA Negeri 1 Bandongan. This research is a pre experimental research, using the formof One Group Pretest and Posttest Design.Data in this research is taken with the test technique. Subjects in this study were allparticipants extracurricular bolavoli SMA Negeri 1 Bandongan amounting to 15 students. While the test instrument used isa test of bolavoli playing skills (Braddy volley ball test) with the coefficient validity of 0.86 while the reliability coefficient 0.93.Data analysis uses t test statistical calculation (t-test), through test of normality test prerequisite, and homogeneity test.The results of this study conclude that: (1) There is a significant (significance) effect between pre-test and post-test of drillmethod on improving the bolavoli playing skills of extracurricular participants bolavoli SMA Negeri 1 Bandongan with preetestand post-test thitung (- 1,904) and ttable (1.76) with significance value (0.05) <0.078. (2) The magnitude of change inbolavoli playing skills averaged -4.333 compared to before the exercise.